2023
DOI: 10.3390/v15081746
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Imaging Sheds Light on the Susceptibility and Permissivity of Carassius auratus to Cyprinid Herpesvirus 2 According to Developmental Stage

Abstract: Cyprinid herpesvirus 2 (CyHV-2) is a virus that causes mass mortality in economically important Carassius spp. However, there have been no comprehensive studies into host susceptibility or permissivity with respect to developmental stage, and the major portal of viral entry into the host is still unclear. To help bridge these knowledge gaps, we developed the first ever recombinant strain of CyHV-2 expressing bioluminescent and fluorescent reporter genes. Infection of Carassius auratus hosts with this recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(104 reference statements)
1
1
0
Order By: Relevance
“…The results indicated that the fin had the highest virus load at 1 dpv in all vaccinated groups, suggesting that the epidermis is a portal of entry and early propagation site of the vaccine virus as previously described for a gibel carp isolate by He et al. (2023). The results also showed that 25°C is the optimal growth temperature for the vaccine in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 79%
“…The results indicated that the fin had the highest virus load at 1 dpv in all vaccinated groups, suggesting that the epidermis is a portal of entry and early propagation site of the vaccine virus as previously described for a gibel carp isolate by He et al. (2023). The results also showed that 25°C is the optimal growth temperature for the vaccine in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 79%
“…Results showed that only juvenile goldfish weighing 8 ± 2 g (one year old) exhibited mortality, possibly due to other varieties’ stronger disease resistance resulting from selective breeding. A recent study indicates that, although CyHV-2 showed a higher susceptibility in adult goldfish, it was more permissive to replication in larvae, resulting in rapid systemic infection and high mortality in juvenile goldfish [ 50 ]. Moreover, prolonged immersion in virus-contaminated water is more likely to induce acute mortality in goldfish.…”
Section: Resultsmentioning
confidence: 99%
“…In the original publication [1], some citation errors were accidentally introduced to this article during the finalizing stage, and therefore these errors were not attributed to the authors. The authors state that the scientific conclusions are unaffected.…”
Section: Missing Citationmentioning
confidence: 99%